Global patterns and trends in the use and management of commercial NTFPs: implications for livelihoods and conservation - Belcher, B.; Ruíz Pérez, M.; Achdiawan, R. (2005)
Understanding of the role and potential of nontimber forest products (NTFPs) for livelihood improvement and conservation has been hindered by a lack of a clear theoretical framework and a functional typology of cases. To help fill this gap, we did a comparative analysis of 61 cases of commercial NTFP production in Africa, Asia, and Latin America. Cases were documented using a standardized set of descriptors organized into categories describing various aspects of the production-to-consumption system. Exploratory analysis yielded useful case groupings by (a) household economic strategy and (b) NTFP production strategy. These groups and their key characteristics are used as a basis for discussing the development and conservation implications of NTFPs.